Eye Symptoms in Parathyroid Disorders: Clinical Presentation and Research Perspectives - Zagórski, Karol; Skalska-Dziobek, Nina; Cetnarowski, Przemysław; Kozik, Mateusz; Małagocka, Weronika; Chybowska, Karolina; Naruszewicz, Maria (Quality in Sport, 2025)
Introduction and purpose: Endocrine disorders often affect multiple organs, frequently presenting with characteristic ophthalmic symptoms. Ocular abnormalities occur in both hyperparathyroidism and hypoparathyroidism, potentially affecting nearly all parts of the eyeball and orbital structures. This study aims to summarize available literature and recent findings on ophthalmic manifestations linked to parathyroid disorders. Material and methods: A comprehensive literature review was conducted using keywords in the PubMed database, the Via Medica journal database, the Polish Society of Endocrinology guidelines, and the Polish Ophthalmological Society guidelines. State of knowledge: Ophthalmic manifestations are common in parathyroid disorders. Hypoparathyroidism often causes cataracts, periorbital tetany, blepharospasm, and optic nerve issues, while congenital cases may involve microphthalmia and corneal opacities. Hyperparathyroidism leads to calcium deposition, affecting retinal arterioles, sclera, eyelids, and cornea, with reports of scleritis and orbital brown tumors. Summary: Recognizing ocular signs of parathyroid diseases aids in diagnosing endocrine disorders and highlights the need for ophthalmological consultation to improve early detection and treatment.